THE EFFECTIVENESS OF APPLICATION OF ELECTRONIC-BASED NURSING DOCUMENTATION IN IMPROVING HEALTH SERVICES : LITERATURE REVIEW - Fatimatuzzahra khairunisa (Indonesian Journal of Community Health Nursing, 2023)
Introduction: Documentation is a nursing record as evidence reporting in the interest of health workers providing health services. The development of nursing care standards with electronic nursing documentation that is in line with technological developments can reduce errors in performing intervention actions on patients. This research aims to improve the quality of documentation to make it easier for nurses to provide health services.   Method: The design of this research is a literature review. The article search was conducted on 10-22 February by accessing five electronic databases (Scopus, Science Direct, Pubmed, Ebscohost and ProQuest). The method used to summarize the journal is CASP (Critical Appraisal Skill Program) tools. The strategy in searching for articles using PICO is, Population: The sample in this study is a number of nurses in the room with varying numbers. Intervention: electronic-based nursing documentation, Comparison: manual nursing documentation. Outcomes: A total of 13 articles were analyzed according to inclusion and exclusion criteria focusing on nursing documentation.   Results: Studies related to electronic documentation show that there is electronic documentation and manual documentation. The use of electronic documentation can improve documentation filling, increase time effectiveness and improve quality nursing service.   Conclusion: Electronic-based nursing documentation is easy to apply efficiently by nurses in the documentation system so that there is an increase in recording or documentation compared to a written system considering the nurse's workload high and time constraint. Keywords: electronic documentation; health services; nurse